Bilingualism effects on cognition in autistic children are not all-or-nothing: The role of socioeconomic status in intellectual skills in bilingual autistic children. (November 2022) - Peristeri, Eleni; Silleresi, Silvia; Tsimpli, Ianthi Maria
Children with autism often display discrepancies in their intellectual functioning, with nonverbal skills frequently being more developed than verbal. Compared to monolingual autistic children, however, much less is known about how bilingualism affects intelligence in autism. The current study examined the intelligence profiles of 146 bilingual and 170 age- and gender-matched monolingual children with autism (6–17 years) using the Wechsler Intelligence Scales for Children-Third Edition, by tracking cluster profiles across children and by modeling verbal and nonverbal IQ performance in each cluster as a function of language experience (monolinguals vs bilinguals), socioeconomic status, and age. The results reveal that socioeconomic status, operationalized as mother's years of education, mediated by bilingualism was strongly related to autistic children's intelligence. Low-socioeconomic status bilingual autistic children exhibited better performance than their monolingual peers across both the verbal and nonverbal intelligence subtests. However, the difference found in the intelligence profiles between monolinguals and bilinguals belonging to high-socioeconomic status was limited to the Comprehension Wechsler Intelligence Scales for Children test, with high-socioeconomic status monolingual autistic children outperforming their bilingual peers. The findings highlight the importance of investigating bilingualism effects in relation to socioeconomic status in autism. Lay abstract: Previous research has suggested that bilingualism may improve cognition in children with autism, and that this boost may stem from improvement in executive functions. The Wechsler Intelligence Scales for Children are considered to be reliable and valid measures of intelligence when administered to autistic children. These measures have so far revealed unusual psychometric properties in monolingual autistic children, notably distinctive patterns of strengths and weaknesses and low inter-correlation among verbal and nonverbal IQ subtests. The way bilingualism affects the intellectual functioning of autistic children has not been explored yet. Nor has there been a satisfactory factor structure that explains monolingual and bilingual autistic children's IQ performance in terms of individual factors, such as age and socioeconomic status. The current study examined the intelligence profiles of 316 bilingual and age- and gender-matched monolingual children with autism using the Wechsler Intelligence Scales for Children–Third Edition. The study applied clustering models to extract intelligence subtypes of autism, and mediation analyses to examine potential mediation effects of age and socioeconomic status on the children's verbal and nonverbal IQ performance. The results support the mediational role of the children's socioeconomic status in the association between bilingualism and intelligence. Low-socioeconomic status bilingual autistic children outperformed their monolingual peers on both verbal and nonverbal subtests, while the differences faded in medium-socioeconomic status and high-socioeconomic status children. The findings emphasize the positive effects of bilingualism on low-socioeconomic status autistic children's intelligence and also highlight high-socioeconomic status as a factor that may mitigate discrepant patterns of strengths and weaknesses in monolingual children's IQ performance.